2019
DOI: 10.1021/acsanm.9b01842
|View full text |Cite
|
Sign up to set email alerts
|

NiCo Alloy/Carbon Nanorods Decorated with Carbon Nanotubes for Microwave Absorption

Abstract: Fabricating high-performance electromagnetic absorbents with strong absorbing intensity and wide effective absorbing bandwidth at low filler loading is still a challenge. Herein, hierarchical NiCo alloy/carbon nanorod@carbon nanotube (NiCo alloy/carbon nanorod@CNT) structures were prepared by a carbonization process using NiCo-MOF-74 nanorods as precursors in Ar flow, in which the aspect ratio of the NiCo alloy/carbon nanorod and the coating density of the CNTs could be easily controlled by the ratio of Ni/Co … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(71 citation statements)
references
References 48 publications
2
69
0
Order By: Relevance
“…In this article, we found that, unlike other MOF derived carbon materials with single‐stage or double‐stage porous structure, 22,24–26 our CD‐MOF derived carbon has a hierarchical(three‐stage) porous structure, containing micro‐, meso‐, and macro‐pores simultaneously. In order to guide the preparation of CD‐MOF derived HPC, the relationship between the morphological properties and prepared conditions is studied in this article.…”
Section: Introductionmentioning
confidence: 87%
“…In this article, we found that, unlike other MOF derived carbon materials with single‐stage or double‐stage porous structure, 22,24–26 our CD‐MOF derived carbon has a hierarchical(three‐stage) porous structure, containing micro‐, meso‐, and macro‐pores simultaneously. In order to guide the preparation of CD‐MOF derived HPC, the relationship between the morphological properties and prepared conditions is studied in this article.…”
Section: Introductionmentioning
confidence: 87%
“…At this point, metal alloys came into the research range due to excellent permittivity and permeability, with NiCo alloys being the most notable [ 17 , 18 ]. NiCo alloys possess the characteristics of high-temperature calcination resistance, oxidation resistance, corrosion resistance, and easy extraction [ 19 , 20 ], and are widely used in high-tech fields such as aerospace.…”
Section: Introductionmentioning
confidence: 99%
“…Shown in Figure 4a, its XRD pattern demonstrates three diffraction peaks at 44.4°, 51.8°, and 76.2°, which are assigned to Ni 2 Co crystals. [30] Also supported by XPS analysis in Figure 4e,f, the decomposition of the Ni 2p 3/2 and Co 2p 3/2 spectra both reveals two peaks, a major one corresponding to the metallic state and a minor one associated with Ni 2+ or Co 2+ , indicating that there is a thin layer of oxide on the surface of these Ni 2 Co alloy nanoparticles. [30] The pyrolysis of Ni 2 Co-Phy nanoshell, as depicted in Figure 3d-f Interestingly, compared with the fragile thin carbon nanoshell in the afore-mentioned C-Ni 2 Co, the nanoshell in this sample seems much more robust and has obviously higher image contrast under TEM observation, and its shell thickness is ≈20 nm, much thicker than the carbon nanoshell in the C-Ni 2 Co sample (Figure S5, Supporting Information).…”
Section: Formation Of Multi-functional Hollow Carbon Nanoshellsmentioning
confidence: 59%